2020
DOI: 10.1111/bdi.12875
|View full text |Cite
|
Sign up to set email alerts
|

A specific group of patients with diagnostic conversion from depression to bipolar disorder and finally to dementia as a mental GSK‐3 disease: A hypothesis

Abstract: Clinically, we have experienced a specific group of patients whose diagnoses changed from unipolar depression to bipolar disorder, and finally to dementia. In this short review, we propose a hypothesis that a genetic glycogen synthase kinase-3 (GSK-3) abnormality may be a common etiological factor in these diseases and in diagnostic conversions. | DEPRE SS I ON TO B IP OL AR D ISORDERA substantial portion of patients with unipolar depression experience diagnostic conversion to bipolar disorder. For example, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, operationally diagnosed bipolar II depression may be latent bipolar I depression, true bipolar II depression, or depression with false hypomanic episodes (which is misdiagnosis for mood elevation within euthymic mood) (Figure 2). To clarify this, longitudinal observation is essential, because not a few patients with depression will present with manic and/or hypomanic episodes, resulting in a change of diagnosis to bipolar disorder (Terao et al., 2020). In addition, it is very difficult to determine whether antidepressants can be used in individual patients with bipolar depression.…”
Section: Deliberate Administration Of Ssris To Treat Bipolar Depressionmentioning
confidence: 99%
“…Furthermore, operationally diagnosed bipolar II depression may be latent bipolar I depression, true bipolar II depression, or depression with false hypomanic episodes (which is misdiagnosis for mood elevation within euthymic mood) (Figure 2). To clarify this, longitudinal observation is essential, because not a few patients with depression will present with manic and/or hypomanic episodes, resulting in a change of diagnosis to bipolar disorder (Terao et al., 2020). In addition, it is very difficult to determine whether antidepressants can be used in individual patients with bipolar depression.…”
Section: Deliberate Administration Of Ssris To Treat Bipolar Depressionmentioning
confidence: 99%
“…Furthermore, patients with bipolar disorder may suffer from two influencing states, a manic (or hypomanic) state or a depressive episode, both of which may increase the risk of dementia [ 37 ]. One study even indicated a specific genetic influence on the relationship between bipolar disorder and dementia [ 38 ]. Further studies need to be conducted to analyze these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human patients suggested that GSK-3 may be a risk gene in BD, since increased protein levels of GSK-3α/β and increased GSK-3β activity could be detected in peripheral blood cells of BD patients (Li et al, 2010;Munkholm et al, 2018). Similarly, elevated GSK-3β mRNA levels were measured in the hippocampus of patients with major depression (Oh et al, 2010), and polymorphisms in the GSK-3β gene were reported in individuals with BD and major depression (Saus et al, 2011;Terao et al, 2020;, and could be correlated with a therapeutic response to lithium (Benedetti et al, 2005). In this context, a GSK-3 polymorphism associated with insomnia in depressed patients (Costemale-Lacoste et al, 2018), also correlates with sleep disturbance in BD patients (Lamont et al, 2010).…”
Section: Psychiatric Disorders Bipolar and Mood Disordersmentioning
confidence: 99%